2018
DOI: 10.1007/s00394-018-1658-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term unprocessed and processed red meat consumption and risk of chronic obstructive pulmonary disease: a prospective cohort study of women

Abstract: Purpose Limited studies have examined red meat consumption in relation to risk of chronic obstructive pulmonary disease (COPD), and none have examined the impact of long-term diet on COPD risk. We sought to investigate the association between long-term red meat consumption and risk of COPD. Methods The population-based prospective Swedish Mammography Cohort included 34,053 women, aged 48-83 years, followed for the current analyses from 2002 to 2014. Unprocessed and processed red meat consumption was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Vegetables and fruits are high in antioxidants, and fish and nuts are high in omega-3 fatty acids, whereas red meat is high in omega-6 fatty acids. The protective effect of vegetables, fruits, and fish and the deleterious effect of red meat in the development of COPD have been demonstrated in several studies (5,6,11,(34)(35)(36)(37)(38)(39)(40). The effect of processed meat such as sausage and cured meat has also garnered attention due to their high content of food additives such as nitrites, and it has been proposed that these additives may cause oxidative stress in the lung (39).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables and fruits are high in antioxidants, and fish and nuts are high in omega-3 fatty acids, whereas red meat is high in omega-6 fatty acids. The protective effect of vegetables, fruits, and fish and the deleterious effect of red meat in the development of COPD have been demonstrated in several studies (5,6,11,(34)(35)(36)(37)(38)(39)(40). The effect of processed meat such as sausage and cured meat has also garnered attention due to their high content of food additives such as nitrites, and it has been proposed that these additives may cause oxidative stress in the lung (39).…”
Section: Discussionmentioning
confidence: 99%
“…High processed meat intake is a risk factor not only for cancer, but also for several chronic diseases and all-cause mortality [19], [20]. Regarding lung health, eight studies have reported that frequent processed meat intake was associated with decreased lung function [6], [7] and greater COPD symptoms [10], exacerbations [11], or incidence [6], [7], [12], [13]. These eight studies have been published either with cross-sectional or longitudinal designs, in different countries, among men or women with a mean age greater than 65 years, and they are all concordant with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade ago, our group (and others) hypothesised that processed meat intake might be an independent dietary risk factor for the development of COPD [6], [7]. Six studies have since been conducted, either among women or men, and they all confirmed that frequent processed meat intake was associated with decreased lung function [8], [9] and greater COPD symptoms [10], exacerbations [11], or incidence [12], [13]. To the best of our knowledge, this association has never been investigated in a younger cohort.…”
Section: Introductionmentioning
confidence: 86%
“…[124,125]. Importantly, more recent large Swedish population-based prospective studies confirmed this detrimental effect for both baseline and long-term consumption of processed (not unprocessed) red meat [126,127]. Another study found that cured meat intake increased the risk of COPD readmission [128].…”
Section: Individual Foods and Nutrients Lung Function And Copdmentioning
confidence: 99%